Angiopoietin-2 May Be Involved in the Resistance to Bevacizumab in Recurrent Glioblastoma. (2nd January 2016) - Labussière, Marianne; Cheneau, Caroline; Prahst, Claudia; Gállego Pérez-Larraya, Jaime; Farina, Patrizia; Lombardi, Giuseppe; Mokhtari, Karima; Rahimian, Amithys; Delattre, Jean-Yves; Eichmann, Anne; Sanson, Marc
ABSTRACT: Despite encouraging response rate of bevacizumab (BVZ) in recurrent glioblastoma, many patients do not respond to this schedule and most of the responders develop an early relapse. Plasma concentrations of VEGF, PlGF, Ang2, and sTie2 were assessed by ELISA before and during BVZ treatment in seventy patients. Baseline levels of VEGF-A, and PlGF were higher in patients than in healthy volunteers, whereas no difference was found for Ang2, and sTie2. No biomarker at baseline was associated with response, PFS or OS. At recurrence, the authors observed an increase of Ang2 suggesting that Ang2/sTie2 could be involved in the resistance to BVZ.